Light Weighted Mutual Authentication and Dynamic Key Encryption for IoT Devices Applications - Sachan, Anuj; Kumar, Dr. Neetesh; Adwiteeya, Adwiteeya (2019 International Conference on Issues and Challenges in Intelligent Computing Techniques (ICICT), 2019)
The unambiguous and unseamed integration of mixed and non-identical end systems are offered by the Internet of Things (IoT). It has been greatly used in many applications such as network automobile, micro-controller, smart farming, smart retail, wearable devices, and industrial internet. In these applications, a substantial number of IoT devices are established that can sense, actuate, evaluate and publicize. There could be a possible violation of the IoT devices also by capturing the servers or the sensors that is, an intruder may affect the sensor and record false data, or an intruder may capture the servers and incorrectly actuate sensors. Therefore, there is significant need of an strong but light weighted mutual authentication scheme. Following this, authentication is done before the data exchange among sensors and the server. Moreover, due to limited capacity of batteries in IoT devices, the mutual authentication protocol is expected to be light weighted. This work proposed an authentication scheme by using the dynamic cipher along with the existing public key encryption, where the client generates the key dynamically, which can only be solved by brute force. The key which is dynamically generated using random function is used for encryption and decryption. Further, an enhancement to the security is proposed by introducing dynamic cipher based authentication. The proposed scheme is evaluated in software environments i.e., IPv6 over low-power wireless personal area networks (6LoWPAN) which is widely used for IoT applications.